EFFECT OF HEALTH EDUCATION ON STUDENT KNOWLEDGE IN DEALING DISASTER IN SD PADOKAN BANTUL YOGYAKARTA - Masta Hutasoit (JURNAL WACANA KESEHATAN, 2018)
Background: Bantul is one of the areas in Yogyakarta that is at risk of disaster. The results of interviews with the head of SD N 2 Padokan found that the school had never had any training on disaster and not yet implemented the curriculum on disaster mitigation. Children are age groups that are very vulnerable to the impact of both physical and psychological disasters. Knowledge of disaster preparedness is important for disaster preventionThe purpose of the study: to determine the effect of health education on knowledge of student preparedness to earthquake disaster events in SD N 2 Padokan, Bantul.Method: This research is quantitative research with quasi experiment design. The design used was pre test and post test nonequivalent control group. The number of samples in the intervention group and the control group were 27 students of class V. The sampling were collected by purposive sampling according to the criteria. Methods of data collection using questionnaires and using nonparametric statistical analysis Wilcoxon with the help of SPSS v.17 for Windows program.Results: The results showed no effect of health education on earthquake disaster preparedness knowledge in SD N 2 Padokan obtained p value 0.480 with α 0.05. In the intervention group the difference of knowledge before and after is indicated by p value 0.180, while for the control group 1,000.Conclusion: there is no effect of health education on disaster preparedness knowledge in SD N 2 Padokan.